Dietary folic acid prevents peripheral neuropathy in mouse models of neural tube defects and type 2 diabetes - Joydeep Chakraborty; Adhideb Ghosh; Eunice B. Awuah; Sally P. Stabler; Martha S. Field; Regan L. Bailey; Patrick J. Stover (Proceedings of the National Academy of Sciences, 2026)
Folate-mediated one-carbon metabolism is implicated in several pathologies including neural tube defects (NTDs), cancer, and neurodegenerative disorders, whereas diabetes is associated with NTDs and peripheral neuropathy (PN). The development of peripheral neuropathy was assessed in Shmt1 +/− and Shmt1 −/− mice, which are models of human folic acid–responsive NTDs, and diabetic ( Lepr db ) mice to determine whether NTDs and PN have a shared etiology. From 6 wk of age, male and female mice with reduced Shmt1 expression exhibited PN, with greater severity in females compared to males. The neuropathic progression was distinct from diabetic peripheral neuropathy (DPN) observed in Lepr db mice. Excess dietary folic acid prevented PN in both Shmt1 −/− and Lepr db/db mice, whereas dietary uridine caused demyelinating PN in mice independent of genotype and folate status. The transcriptome from L3-L5 dorsal root ganglia (DRG) exhibited distinct sex-specific differences in glial cell gene expression when comparing Shmt1 +/+ and Shmt1 −/− mice. DRG sensory neurons exhibited changes in the expression of solute carriers and ion channels involved in nociception, neurotransmission, and structural support. We conclude that reduced thymidylate synthesis causes folic acid–responsive NTDs and PN in mice and that diabetes sensitizes mice to folic acid–responsive PN. Diabetes induces a special nutritional requirement for high intake of folic acid to prevent PN.